2022
DOI: 10.3389/fimmu.2022.826515
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathophysiological Roles of Metabolic Pathways for NET Formation and Other Neutrophil Functions

Abstract: Neutrophils are the most numerous cells in the leukocyte population and essential for innate immunity. To limit their effector functions, neutrophils are able to modulate glycolysis and other cellular metabolic pathways. These metabolic pathways are essential not only for energy usage, but also for specialized effector actions, such as the production of reactive oxygen species (ROS), chemotaxis, phagocytosis, degranulation, and the formation of neutrophil extracellular traps (NETs). It has been demonstrated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 228 publications
(386 reference statements)
0
31
0
Order By: Relevance
“…These cells respond rapidly to infection and injury in various tissues. They represent the first line of defense and utilize multiple mechanisms of oxygen-dependent and oxygen-independent processes to protect against infection, including phagocytosis, cytokine secretion, and reactive oxygen species production [ 60 , 61 ]. Thus, neutrophils represent a potential target for the development of novel anti-inflammatory therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…These cells respond rapidly to infection and injury in various tissues. They represent the first line of defense and utilize multiple mechanisms of oxygen-dependent and oxygen-independent processes to protect against infection, including phagocytosis, cytokine secretion, and reactive oxygen species production [ 60 , 61 ]. Thus, neutrophils represent a potential target for the development of novel anti-inflammatory therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils are the most abundant leukocyte and are vital for innate immunity [ 55 ]. These cells are the first responders to infection and injury in various tissues, establishing the first line of defense through multiple mechanisms such as phagocytosis, cytokine secretion, and reactive oxygen species production [ 56 , 57 ]. Thus, neutrophils represent an ideal pharmacological target for therapeutic development, and numerous natural products, including essential oils, have been shown to exhibit neutrophil immunomodulatory activity [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both mitochondrial [ 265 , 266 ] and nuclear DNA [ 262 ] have been found to form or at least make up parts of NETs. As reviewed elsewhere [ 267 , 268 , 269 ], the details of the different pathways involved in NET formation is still rather controversial and highly debated. With this in mind, we briefly describe what is known to date about the mechanisms of formation ( Figure 6 ).…”
Section: Other Sources Of Cell-free Dnamentioning
confidence: 99%
“…In 2009 Yousefi et al demonstrated that NETs from viable neutrophils can also be composed of mtDNA. Two modes of mitochondrial NET formation/extrusion have been suggested so far: (a) mtDNA may be released into cytosol where it is further packed into vesicles and released by fusion with the plasma membrane thereby forming traps [ 275 ]; (b) The direct release of mtDNA and granules in a catapult-like manner via fusion of the mitochondrial and plasma membrane [ 269 , 271 , 275 ].…”
Section: Other Sources Of Cell-free Dnamentioning
confidence: 99%